(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The Bisection, Newton, and Secant Methods are indicated for demonstrating the numerical approximation of the non-linear equation problem f(x) = ex + 2−x + 2 cos(x) − 6 = 0 . the paper wants to display the comparison of implementation, the convergence rate among methods of detect the root of the non-linear equation. The MATLAB R2015b is used to determine the root-finding problem within the desired closed interval [1, 2] and illustrate the numerical solution compared. The Newton and Secant are speedy to converge with very small error part and requiring a few steps of iterations while the bisection method is converged with taking too much computingof iterations. Consequently, the numerical approximation solution of the methods on the sample problem interprets that the Newton and Secant are more absolutely accurate and efficient than the results achieved from the Bisection method.